Transformation of District/City Response Patterns for Child Protection during Post Covid-19, Case Study of Central Java Province, Indonesia - Wijaya, M. Indra Hadi; Agushybana, Farid; Jati, Sutopo Patria; Ariani, Nofa Martina; Purnami, Cahya Tri; Salma, Salma; Lisnawati, Naintina; Rahman, Amni Zarkasyi; Imawan, Satria Aji (Populasi, 2024)
Covid-19 for three years has become an inseparable part of the lives of urban and rural communities. The impact occurs, such as the impact of Covid-19 on children. Children are a vulnerable part of society during a pandemic, about the conditions for their health, education, and protection. The role of the city in carrying out its duties as a public servant is important, where all stakeholders have an important role. Central Java, one of the provinces affected by Covid-19 has responded well with its adaptive programs. This research was conducted with a quantitative approach with a quantitative descriptive method, starting with an analysis of the role of stakeholders and programs related to Covid-19 prevention for children. The results of the analysis are continued by looking at the spatial pattern between cities and districts. Research data is taken from primary surveys through FGD and document review. The results of the study identify that not all city/district areas have a response to child protection during the Covid-19 pandemic, urban areas are more responsive to this condition. Increasing the role of protection for children during a pandemic is an important part of the process of returning to the new normal.